[Sorting citrus] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Sorting of citrus at La Gloria Estate.
Cataloger's title
Keywords: Citrus fruits -- Trinidad and Tobago